Om samfundsreligionen - Riis, Ole (Religionsvidenskabeligt Tidsskrift, 1985)
The concept of civil religion was coined by Rousseau and revived by Bellah in order to identify the basis of religious legitimization in a voluntaristic society. In the Danish context, the status of the Lutheran “folk-church” becomes central in a debate concerning the Danish civil religion. But whereas the state supports the Lutheran folk-church and vice versa, the folk-church should not be identified with the civil religion. There is, however, a wing in church policy, which seeks to use the Lutheran church as a basis for the integration of Danish society and the legitimization of the political institutions. A civil religious church policy should not be confused with the proper civil religions. The civil religious church policy tends, on the one hand, to dissolve the theological content of the Lutheran church, and, on the other, to evade the critical potential of the concept of civil religion (as expressed in Bellah’s The Broken Covenant). There exist, certainly, a civil religion in Denmark. Its national mythology was mainly expressed by Grundtvig, in the years of national crisis and the formation of the democratic constitution. The national mythology was spread to the populace in general via the free high school system. It hints at a special covenant between God and the Danes: the Danish people have a historical calling to spread a pattern of human values, i.e. solidarity with the poor, freedom under a social responsibility, and so on. The national mythology is still functioning. But it has weakened and changed character. New myths and new heroes are taking over – sports heroes among others. The national ecstasy during the Danish participation in the European football championship parallels Durkheim’s description of the ritual of the Arunta – and thus the elementary forms of the religious life.